Սննդային հավելումները և մարդու առողջությունը - Մարգարյան, Թ. Ս. (Հայաստանի ԳԱԱ)
В деле образования и воспитания личности огромную роль играет забота о собственном здоровье, развитие подходов к чувству ответственности по отношению к нему. В этом случае большое значение имеет среда, в которой данная личность получает образование и воспитание. В сохранении здоровья большую роль играет пища, с помощью которой человек получает энергию для своей изнедеятельности. While educatig and growing up a person, the personal health care, the development of high responsibility levels play an important role. From this point of view the role of the environment, where a person was educated and grown up, is great. Food has a great role in the health care as a human get all the necessary energy for his/her vital activity from it. What kind of food do we use, what additions does it contain, how do theyinfluence on our health? Do they promote the health improvment or spoil it.
Keywords: Բժշկագիտություն; Առողջապահություն; Բժշկություն